Chronic urticaria: Pharmacological treatment (International Seven Journal of Health Research, 2023)
Introduction: Chronic urticaria is a skin condition characterized by recurrent episodes of itching and rashes that persist for more than six weeks. Its effective management is essential for improving patients' quality of life. This study aims to evaluate best practices in the management of chronic urticaria. Objectives: To evaluate the most effective treatment options available for patients with chronic urticaria. Methodology: A literature review was carried out, including clinical studies and recent medical guidelines. Treatment options, diagnosis, drug safety and efficacy, and management strategies in different age groups were analyzed. Results: The results of this review highlight that non-sedating H1 antihistamines are the first line of treatment for chronic urticaria. In cases of treatment resistance, other options such as systemic corticosteroids and immunosuppressants can be considered, although with caution due to potential side effects. In elderly patients, liver and kidney function should be considered when choosing medications. In addition, identifying possible underlying causes is crucial for the effective management of chronic urticaria. Conclusion: The management of chronic urticaria requires a personalized approach based on an assessment of the patient's needs, considering age, comorbidities and drug safety. Identifying and treating the underlying causes, where possible, is essential. With current guidelines and therapeutic options, it is possible to significantly improve the quality of life of patients with chronic urticaria.